2023
DOI: 10.1519/jsc.0000000000004423
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Contrast Training and Progressive Resistance Training on Strength and Power-Related Measures in Subelite Australian Rules Football Players

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Numerous studies indicate that plyometric training is an effective exercise for optimizing athlete power compared to other forms of training. In addition to plyometric training, several studies have shown significant increases in power through vertical jump (VJ) when combining resistance training loading in one session with contrast strength training (Cormier, Freitas, Rubio-Arias, & Alcaraz, 2020;Hammami, Gaamouri, Shephard, & Chelly, 2019;Schneiker, Fyfe, Teo, & Bishop, 2023). Interestingly, our study revealed that resistance training combined with volleyball skills training alone (EG), or skills training alone (CG), were sufficient to enhance athletes' power, as evidenced by the VJ results, without involving plyometrics or contrast training methods.…”
Section: Discussionmentioning
confidence: 55%
“…Numerous studies indicate that plyometric training is an effective exercise for optimizing athlete power compared to other forms of training. In addition to plyometric training, several studies have shown significant increases in power through vertical jump (VJ) when combining resistance training loading in one session with contrast strength training (Cormier, Freitas, Rubio-Arias, & Alcaraz, 2020;Hammami, Gaamouri, Shephard, & Chelly, 2019;Schneiker, Fyfe, Teo, & Bishop, 2023). Interestingly, our study revealed that resistance training combined with volleyball skills training alone (EG), or skills training alone (CG), were sufficient to enhance athletes' power, as evidenced by the VJ results, without involving plyometrics or contrast training methods.…”
Section: Discussionmentioning
confidence: 55%
“…height or weight) when concluding how an absolute measure (e.g. of muscular strength) will translate into actual athletic ability [45][46][47][48][49]. Despite this, Hilton and Lundberg's [3] literature prioritise absolute rather than relative data, failing to normalise their results to either height or mass.…”
Section: Underlying Assumptionsmentioning
confidence: 99%